Peran Pendamping Desa Dalam Model Pemberdayaan Masyarakat Berkelanjutan - Bambang Suswanto; Rili Windiasih; Adhi Iman Sulaiman; Sri Weningsih (JUSS (Jurnal Sosial Soedirman), 2018)
Rural development has becomes the key and foundation of regional and national development, so that the role of village facilitators was expected to accelerate the backwardness and prosperity of the community. The aims of the study tto analyze the role of village facilitators in a sustainable community empowerment model. The research used qualitative Participatory Rural Appraisal (PRA) methods, data were collected through direct observation, documentation analysis, and in-depth interviews. The informants by purposive determination, consisting of village facilitators, especially accompaniment scholars and professional assistants, cadres of village community empowerment, village government, activists and community leaders. Data analysis of PRA through triangulation, categorization and investigation. The research took place in the village of Pasuruhan, Binangun district, Cilacap Regency.. The result showed that the village facilitators are important and needed in addition to administrative and financial management of village development, as well as for the implementation of sustainable community empowerment, starting from planning, implementation, monitoring, evaluation, partnership and self-reliance. The village facilitators need coordination and cooperation to creat communication forums and team work to review the problems, potentials and prospects in rural development.